Investigating the Role of Ly6G+ Neutrophils in Incisional and Inflammatory Pain by Multidimensional Pain-Related Behavioral Assessments: Bridging the Translational Gap - Segelcke, Daniel; Pradier, Bruno; Reichl, Sylvia; Schäfer, Lukas C.; Pogatzki-Zahn, Esther M. (Frontiers in Pain Research, 2021)
In recent years, preclinical pain research has failed to develop genuinely new analgesics for clinical use. This fact is reflected by a high number of patients, limited drug efficacy accompanied by side effects, and a long-term opioid intake. Two main aspects have been addressed, which hinder translation: the use of non-relevant pain models and a mismatch between pain-related outcomes in preclinical and clinical studies. Conversely, disease-specific pain models that mirror more closely the clinical situation and multidimensional behavioral outcome measures that objectively and reproducibly assess relevant pain-related symptoms in a preclinical setting could improve translation. Mechanistically, a matter of debate is the role of Ly6G+ neutrophil granulocytes (NGs) for pain. NGs are essential to eliminate pathogens and promote the wound healing process. For this purpose, there is a need to release various pro- and anti-inflammatory mediators, some of which could ameliorate or enhance pain. However, the contribution of NGs to different pain entities is contradictory for reflex-based tests, and completely unknown in the context of non-evoked pain (NEP) and movement-evoked pain (MEP). First, we combined withdrawal reflex-based assays with novel video-based assessments for NEP- and MEP-related behavior in two mouse pain models. The pain models utilized in this study were incision (INC) and pathogen/adjuvant-induced inflammation (CFA), translating well to postsurgical and inflammatory pain entities. Second, we depleted NGs and applied a set of behavioral assessments to investigate the role of NG migration in different pain modalities. Our comprehensive behavioral approach identified pain-related behaviors in mice that resemble (NEP) or differentiate (MEP) behavioral trajectories in comparison to mechanical and heat hypersensitivity, thereby indicating modality-dependent mechanisms. Further, we show that injury-induced accumulation of NGs minimally affects pain-related behaviors in both pain models. In conclusion, we report a novel assessment to detect NEP in mice after unilateral injuries using a more unbiased approach. Additionally, we are capable of detecting an antalgic gait for both pain entities with unique trajectories. The different trajectories between MEP and other pain modalities suggest that the underlying mechanisms differ. We further conclude that NGs play a subordinate role in pain-related behaviors in incisional and inflammatory pain.